PETA PENCEGAHAN BULLYING PADA KEGIATAN MATSAMA DI MADRASAH IBTIDAIYAH - Arif Sirojul Mustafid; Ratna Dewi; Mumun Mulyati (STAI ALHIKMAH Jakarta, 2024)
AbstractBullying behavior has a great impact on Madrasah Ibtidaiyah (MI) students. The government has made various efforts to prevent bullying. But in fact, there are still bullying behaviors in schools. This study aims to map efforts to prevent bullying behavior in Matsama (Masa Taaruf Siswa Madrasah) activities at MI Sananul Ula. This type of research is qualitative. Data were obtained from observations and interviews. The subjects of this study were the head of the madrasah, teachers and students of the madrasah. After research, the development of a Matsama program oriented towards bullying prevention carried out at MI Sananul Ula Daraman Bantul Yogyakarta can be mapped into three parts. 1) doctrination, 2) rationalization and 3) evaluation. In the process, there is a process of selecting class leaders who also act as agents of change. AbstrakPerilaku bullying memiliki dampak yang besar bagi siswa Madrasah Ibtidaiyah (MI). Pemerintah telah melakukan berbagai upaya pencegahan bullying. Namun nyatanya masih saja terdapat perilaku bullying di sekolah. Penelitian ini bertujuan untuk memetakan upaya pencegahan perilaku bullying pada kegiatan Matsama (Masa Taaruf Siswa Madrasah) di MI Sananul Ula. Jenis penelitian ini adalah kualitatif. Data diperoleh dari observasi dan wawancara. Subjek penelitian ini adalah kepala madrasah, guru dan siswa madrasah. Setelah dilakukan penelitian, pengembangan program Matsama yang berorientasi pada pencegahan bullying yang dilakukan di MI Sananul Ula Daraman Bantul Yogyakarta dapat dipetakan menjadi tiga bagian. 1) doktrinasi, 2) rasionalisasi dan 3) evaluasi. Dalam prosesnya, terdapat proses pemilihan ketua kelas yang juga bertindak sebagai agen perubahan.